P95 Costimulatory molecules on CMV-specific T-cells in CMV IgG+ patients with systemic lupus erythematosus. (23rd March 2020) - Savidis, Antje; Wilde, Benjamin; Kribben, Andreas; Witzke, Oliver; Dolff, Sebastian
Abstract : Background: Cytomegalovirus (CMV) infection is an uncommon but severe infection in patients with systemic lupus erythematosus (SLE) due to immunosuppressive therapy. Standard prophylaxis with antiviral agents or pre-emptive strategies to monitor viral load are not standard of care. The aim of the present study was to investigate the expression of coinhibitory molecules PD-1 and BTLA-4 on CMV specific T-cells in SLE-patients. Methods: Twenty-three SLE-patients and eight healthy controls were enrolled. Nineteen SLE patients were CMV IgG+, four were CMV IgG-. Peripheral blood was sampled and stimulated with CMV lysate, SEB or control serum in presence of anti-CD28/CD49d. After six hours of stimulation, CD154 expression was determined by flow cytometry on CD3 + T-cells. The coinhibitory molecules PD-1 and BTLA were determined on activated CD154 + CD3 + T-cells. Symptomatic CMV infection was defined as CMV syndrome or tissue invasive disease. Asymptomatic CMV infection was defined as detectable CMV replication in peripheral blood and absence of signs indicating CMV syndrome/tissue invasive disease. Results: PD-1 and BTLA-4 expression was not significantly different on CMV-specific CD154 + CD3 + T-cells in SLE-patients as compared to healthy controls. An analysis according to the CMV serostatus revealed a tendency to a decreased proportion of PD-1 + CD154 + CD3 + T-cells in CMV IgG negative patients as compared to CMV IgG positive. The BTLA-4 expression was significantly decreased on CD154 + CD3 + T-cells in CMV IgG negative patients as compared to CMV IgG positive. Conclusion: SLE-patients show a significant decreased expression of BTLA on CMV-specific T-cells. The co-inhibitors PD-1 and BTLA usually promote T-cell suppression. Thus a decrease may prone to severe symptomatic infections.